Diversion colitis: Aetiology, diagnosis and treatment. A systematic review. Issue 6 (25th October 2020) - Dilke, Stella; Segal, Jonathan; Tozer, Phil; Vaizey, Carolynne; Wilson, Ana
Abstract: Background: Diversion colitis (DC) is an inflammatory disease associated with diversion of the bowel following operative intervention and formation of ostomy. DC has an association with inflammatory bowel disease but is also seen after diversion for rectal cancer, mesenteric ischaemia and trauma. Symptoms include rectal discharge, rectal bleeding and abdominal pain. This article reviews papers concerning treatment, aetiology and diagnosis of DC. Methods: A systematic search of the online databases MEDLINE and EMBASE was included between 1969 and October 2018. A total of 4898 abstracts and 71 full‐text articles were screened with 18 papers included (n = 578). Randomised controlled trials, cohort studies and observational studies investigating the diagnosis, treatment or aetiology of DC were included. Results: Three studies investigated treatments for DC. Of these, colonic irrigation with a fibre solution and twice daily butyrate enemas demonstrated a significant reduction in the endoscopic score of inflammation in the diverted bowel ( P = 0.01 and P = 0.0083 respectively). Several aetiologies for DC were suggested, including an aerobic microbial dysbiosis. One study suggested that a reduction in Bifidobacterium species was associated with reduced severity of DC ( P = 0.005). It was not clear how duration of defunctioning related to the incidence of DC. Conclusion: Whilst there are endoscopic and microscopic changes in the small bowel and colon associated with diversion, a sequence of events leading to the development of DC has not been elucidated. The most striking weakness with these studies was the lack of significant follow‐up and heterogeneity. Larger longitudinal studies would be of benefit.